Forest plantations on cleared agricultural land in Australia : a regional economic analysis - Burns, Kevin; Walker, David; Hansard, Allan W.; Australian Bureau of Agricultural and Resource Economics (Canberra : Australian Bureau of Agricultural and Resource Economics, 1999)
Plantations are increasing in importance domestically and internationally as a source of wood and other products and as a key element in the formulation of forest and environmental policy. Since the launch of the Plantations for Australia: The 2020 Vision, by the Commonwealth government in conjunction with state governments and the forest industry, there has been considerable debate on the future of plantations and farm forestry. Many questions on where, when and how (or even whether) plantations and farm forestry will occur have been raised. This report provides essential information to this debate by providing comprehensive data on plantation potential based on biological, economic and area specific factors for key plantation regions in Australia. The report also provides information on existing and emerging factors that are likely to influence plantation development in the future, including the outlook for forest product markets, technological change, land availability, government regulations and the emergence of new product markets, including the use of plantations for carbon sequestration. This study was funded by the Wood and Paper Industry Strategy to assist in the promotion of a sustainable and internationally competitive wood processing industry through the provision of relevant economic information on the economic potential for expanding Australia's plantation resources.r future de
Funded by Wood and Paper Industry Strategy, Agriculture, Fisheries and Forestry - Australia.
Includes bibliographical references.
Previously also available on the Internet at: http://www.abare.gov.au/pdf/99_11.pdf
Keywords: Tree farms -- Australia -- Economic aspects; Agroforestry -- Australia -- Economic aspects; Forests and forestry -- Australia -- Economic aspects; Land use, Rural -- Australia -- Economic aspects; Plantations -- Australia -- Economic aspects